Intertester reliability of a movement impairment-based classification system for individuals with shoulder pain - Patitta Torwichien; Mantana Vongsirinavarat; Prasert Sakulsriprasert; Sirikarn Somprasong (World Scientific Publishing, 2020)
Background: Other than pathoanatomical diagnosis, physical therapy managements need the diagnosis of movement-related impairments for guiding treatment interventions. The classification system of the Movement System Impairment (MSI) has been adopted to label the musculoskeletal disorders in physical therapy practice. However, reliability study of this classification system in individuals with shoulder pain has not been reported in the literature. Objective: This paper investigated the intertester reliability of the diagnosis based on the MSI classification system in individuals with shoulder pain. Methods: The patients with shoulder pain, between the ages 18-60 years, were recruited if he or she had pain between 30 and 70 on the 100mm visual analog scale for at least three months. The examiners who were two physical therapists with different clinical experiences received a standardized training program. They independently examined 45 patients in random order. Each patient was examined by both therapists on the same day. The standardized examination scheme based on the MSI approach was used. Patients were identified to subgroup syndromes according to scapular and humeral syndromes and also determining their subcategory syndromes. Six scapular subcategory syndromes included downward rotated, depressed, abducted, wing, internal rotated/anterior tilted, and elevated. Three humeral subcategory syndromes were anterior glide, superior glide, and medial rotated. More than one subgroup and subcategory of syndromes could be identified in each patient. The test results of each session were blinded to another therapist. The percentages of agreement and kappa statistic were determined. Results: The results showed that agreement levels in identifying subgroup syndromes was fair (71.11% agreement, kappa coefficient = 0.34) and classifying subcategories syndromes were poor to substantial (73.33-91.11% agreement, kappa coefficient = 0.20-0.66). The overall agreement and kappa value of the MSI classification of subcategory syndromes was poor (kappa coefficient = 0.11; 95% CI 0.05-0.18). The agreement level of subcategories for scapular depression and humeral superior glide syndromes was substantial. The scapular winging, depression, and downward rotation were the three syndromes that were most frequently identified by both the examiners. Conclusion: The intertester reliability between therapists with different experience according to the MSI approach for shoulder pain classification was generally acceptable to poor due to the nature of the classification system. The standardized procedure and intensive training can be used for inculcating novice therapists with adequate level of intertester reliability of examination.